2021
DOI: 10.2147/ndt.s341667
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of the Relationship Between Abnormalities in Vision-Related Brain Networks and Quality of Life in Patients with Migraine without Aura

Abstract: Objective To evaluate whether migraine without aura (MwoA) can be partly attributed to abnormalities of vision-related brain networks (VBN) and whether these specific regional abnormalities affect the patients’ quality of life (QoL). Methods A total of 40 participants, including 20 MwoA patients and 20 healthy control volunteers, were enrolled. There were no significant differences in sex, age, educational qualifications and dominant hand between the two groups. Headach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…On the one hand, the activation of the thalamus, brainstem, and related functional areas such as the cingulate gyrus, insular lobe, and temporal lobe can be observed under task stimulation, indicating that these areas are involved in the pathophysiological process of inducing migraine [ 57 , 58 , 59 ]. On the other hand, abnormal brain networks and functional connections can also be observed in the resting state, including the occipital lobe, the sensorimotor network, bilateral lateral and inferior cerebellum, the cingulo–opercular network, the default mode network, and the frontal–parietal network [ 62 , 63 ]. In recent years, research on the small-world network of migraine patients and the study of dynamic functional connectome patterns both support the idea that the thalamus, occipital lobe, and basal nucleus play a vital role in the process of relaying pain, regulating vision, and integrating pain [ 66 , 67 ].…”
Section: Mri and Migrainementioning
confidence: 99%
“…On the one hand, the activation of the thalamus, brainstem, and related functional areas such as the cingulate gyrus, insular lobe, and temporal lobe can be observed under task stimulation, indicating that these areas are involved in the pathophysiological process of inducing migraine [ 57 , 58 , 59 ]. On the other hand, abnormal brain networks and functional connections can also be observed in the resting state, including the occipital lobe, the sensorimotor network, bilateral lateral and inferior cerebellum, the cingulo–opercular network, the default mode network, and the frontal–parietal network [ 62 , 63 ]. In recent years, research on the small-world network of migraine patients and the study of dynamic functional connectome patterns both support the idea that the thalamus, occipital lobe, and basal nucleus play a vital role in the process of relaying pain, regulating vision, and integrating pain [ 66 , 67 ].…”
Section: Mri and Migrainementioning
confidence: 99%
“…The results revealed that migraineurs exhibited abnormalities in brain areas related to pain, including pain perception areas (e.g., cerebellum and brainstem) and nociceptive inhibition regions (e.g., periaqueductal gray) 8 11 . Meanwhile, migraineurs exhibited abnormalities in sensory-related areas, such as the fusiform gyrus (FFG) and insula 12 15 . Furthermore, other researches also reported unnormal brain regions relating to executive ability and attention in migraineurs, such as the paracentral lobule (PCL) and orbitofrontal gyrus (OFG) 16 19 .…”
Section: Introductionmentioning
confidence: 99%